2009
DOI: 10.1186/1477-7827-7-100
|View full text |Cite
|
Sign up to set email alerts
|

Impact of female age and male infertility on ovarian reserve markers to predict outcome of assisted reproduction technology cycles

Abstract: Background: This study was designed to assess the capability of ovarian reserve markers, including baseline FSH levels, baseline anti-Müllerian hormone (AMH) levels, and antral follicle count (AFC), as predictors of live births during IVF cycles, especially for infertile couples with advanced maternal age and/or male factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 38 publications
3
58
1
5
Order By: Relevance
“…With regard to the ability to identify poor responder women, the analysis demonstrated the AMH is at least as efficient as AFC to predict a high ovarian response [49,50]. Various reports suggest a correlation between low AMH levels and poor ovarian response [28,[50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the ability to identify poor responder women, the analysis demonstrated the AMH is at least as efficient as AFC to predict a high ovarian response [49,50]. Various reports suggest a correlation between low AMH levels and poor ovarian response [28,[50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated plasma AMH levels are associated with better fertility rates (Lee et al 2009). Seifer et al (2002), the first authors reporting an association between serum AMH levels and ovarian response to gonadotrophin, showed that AMH levels were 2.5-fold higher in patients with at least 11 oocytes compared with those with six oocytes or fewer retrieved.…”
Section: Amh and Assisted Reproductive Technologymentioning
confidence: 99%
“…10,11 From the present study, we conclude that age and AMH have negative correlation (r-0.266) ( Figure 1). …”
Section: -40mentioning
confidence: 86%
“…Patients were studied with respect to total number of oocytes, number of mature oocytes, duration of stimulation, total dose of gonadotropins, peak E2 levels, number of embryos and Grade A embryos. According to number of oocytes retreived, patients were divided into poor responders (<3 oocytes) normal responders (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and hyperresponders (>20).…”
Section: Methodsmentioning
confidence: 99%